REMOVED: P 8 Serotonergic antidepressants decrease hedonic signals but leave learning signals in the nucleus accumbens unaffected (Graf et al., 2016). Issue 10 (October 2017) - Graf, H.; Metzger, C.D.; Walter, M.; Abler, B.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been removed at the request of the authors, as they did not give permission for the abstract to be published.